1994
DOI: 10.1111/j.1745-6584.1994.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Surfactant Washing of Polychlorinated Biphenyls and Oils from a Contaminated Field Site: Phase II Pilot Study

Abstract: An in situ surfactant washing process was previously developed and successfully pilot‐tested at a field site contaminated with polychlorinated biphenyls (PCBs) and oils (Abdul et al., 1992). A second phase of the pilot study, conducted the following year at the same site, confirmed the technical viability of this process. The results of the phase II study surpassed the predictions of the long‐term performance of this technology based on the phase I results. Soil cores taken from the plot before the phase I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…Results from several laboratory studies on the use of surfactants for washing hydrophobic contaminants from soils have shown that this enhanced washing method has a good potential [13,21]. Results collated from many papers showed the % of PCE removal [5] between 33 and 85% and total petroleum hydrocarbon (TPH) recoveries between 60 and 90% [22].…”
Section: Introductionmentioning
confidence: 94%
“…Results from several laboratory studies on the use of surfactants for washing hydrophobic contaminants from soils have shown that this enhanced washing method has a good potential [13,21]. Results collated from many papers showed the % of PCE removal [5] between 33 and 85% and total petroleum hydrocarbon (TPH) recoveries between 60 and 90% [22].…”
Section: Introductionmentioning
confidence: 94%
“…Surfactant-enhanced remediation has become a promising techniques to remove nonaqueous phase liquids from soils and aquifers [19,20]. It is a promising innovative technology for the restoration of such contaminated sites.…”
Section: Introductionmentioning
confidence: 99%
“…The following provides some examples of indicative environmental pathways: surfactants are often used in soil-applied agrochemical formulations wherein they may be used to stabilise emulsions or aid the aqueous dispersion of solid carriers and powders (Mulqueen 2003); domestic wastewater containing soaps and surfactants arising from personal cleansing and laundry is increasingly used for irrigation in arid and semi-arid regions (Travis et al 2008;Wiel-Shafran et al 2006); and surfactants may be used as remedial aids for soil clean-up (Abdul and Ang 1994;Abdul et al 1992) Water in the unsaturated zone of preferentially water wetting soils is held in small pores, in pore throats, in the corners and crevices of larger pores and as films around the soil particles (Zhou and Blunt 1997). A pressure drop exists across the curved interface between air and water which results in the water pressure being lower than the air pressure.…”
Section: Introductionmentioning
confidence: 99%